POPULATION PARTICIPATION IN DECISION-MAKING ON RURAL WATER SUPPLY: CASE STUDIES OF THE DISTRICTS OF BOANE AND MANHIÇA (International Seven Journal of Multidisciplinary, 2025)
The present article was elaborated with the objective of analysing the participation of the population in the decision-making process about rural water supply in Mozambique, specifically in Maputo Province, Boane and Manhiça districts. Such analysis was carried out in the light of phenomenological theory, complemented by the spider web model for the analysis of the level of community participation. Regarding to data collection, three techniques were applied, namely documental research, semi-structured interviews and focus group. In this process, the data of 20 semi-structured interviews and 12 focus groups were collected. In the analysis carried out, it was verified that the relatively weak implementation of community inclusion mechanisms by government entities has been leading to a low level of community participation, worsened by the population high rate of illiteracy and their lack perception of the necessity of complying with monthly contribution. Thus, it was concluded that in order to increase the level of community participation  and, consequently, improve the access to rural drinking water, it is necessary to fully implement the community inclusion mechanisms embodied on PRONASAR Program by including these aspects as priorities in the next five-year.